Patient characteristics and disease spectrum in a German vascular anomalies center - Strübing, Felix; Laurich, Annette; Weiß, Christel; Kneser, Ulrich; Schönberg, Stefan; Sadick, Maliha (Acta radiologica, 2024)
Background - Vascular malformations are rare diseases that should be treated in dedicated vascular anomaly centers (VAC). There is only a small amount of data on the diagnostic and therapeutic handling of these patients, before they are referred to a VAC. - Purpose - To demonstrate the disease-specific patient characteristics in a German VAC, which are required to determine diagnostic and therapeutic steps. - Material and Methods - In a retrospective study, all patients who were treated in the VAC from April 2014 until August 2021 were identified. In total, 593 patients were included in this study. - Results - Almost all patients had previously consulted a physician (591/593, 99.7%). A mean of two different physicians had been consulted (range 0-10). Patients with more complex, syndromal vascular malformations had significantly more previous appointments (P = 0.0018). In only 44% (261/593) of patients, the referral diagnosis was made correctly. Most patients had been previously treated for their vascular anomaly: pharmacotherapy (n = 130; 21.9%), compression garments (n = 141; 23.8%), surgical resection (n = 80; 17.3%) and sclerotherapy (n = 68; 11.5%). Fifty-two patients who had been falsely diagnosed had also received therapy prior to their referral to the VAC (8.8%). Most patients received an ultrasound examination in the VAC (n = 464; 78.2%). Most frequently, compression therapy was prescribed (n = 256; 43.2%), followed by sclerotherapy (n = 175, 29.5%) and pharmacotherapy (n = 55; 9.3%). - Conclusion - Patients suffering from vascular anomalies often go through a complicated scheduling with numerous outpatient appointments and have a high risk of misdiagnosis and mistreatment prolonging the medical condition. Therefore, patients with vascular anomalies should be treated in a dedicated vascular anomaly center.
Vorab online veröffentlicht: 24. September 2023
Gesehen am 20.11.2023